Knowledge, attitude and practice regarding pertussis among a public university students in Malaysia - Abdul Basir, Nur Amalina; A. Rahman, Nor Azlina; Haque, Mainul; , (Association of Support to Oral Health Research (APESB), 2020)
Objective: To study the knowledge, attitude, and practice (KAP) regarding pertussis among students in a public university in Malaysia.